2014
DOI: 10.1111/jnu.12116
|View full text |Cite
|
Sign up to set email alerts
|

Novel and Emerging Strategies for Longitudinal Data Collection

Abstract: A better understanding of novel and emerging longitudinal data collection strategies will ultimately improve longitudinal data collection as well as foster research efforts. Nurse researchers, along with all researchers, must be aware of and consider implementing novel and emerging strategies to ensure future healthcare research success.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…Especially at T2, response rates were under 70%. Although such declines in response rates are usual for longitudinal studies (Udtha, Nomie, Yu, & Sanner, 2015), they still affect the representativeness, generalizability and applicability of the sample (Badger & Werrett, 2005).While no nursing textbooks make overall recommendations about desirable rates (Badger & Werrett, 2005), other meta-analyses studies which included nurses (Cho, Johnson, & Vangeest, 2013) have reported an average longitudinal response rate of 51%. Also, by using mixed models instead of ANOVAs, list-wise deletion was avoided.…”
Section: Limitationsmentioning
confidence: 99%
“…Especially at T2, response rates were under 70%. Although such declines in response rates are usual for longitudinal studies (Udtha, Nomie, Yu, & Sanner, 2015), they still affect the representativeness, generalizability and applicability of the sample (Badger & Werrett, 2005).While no nursing textbooks make overall recommendations about desirable rates (Badger & Werrett, 2005), other meta-analyses studies which included nurses (Cho, Johnson, & Vangeest, 2013) have reported an average longitudinal response rate of 51%. Also, by using mixed models instead of ANOVAs, list-wise deletion was avoided.…”
Section: Limitationsmentioning
confidence: 99%
“…For example, the effectiveness of online data collection may be quite dependent on not only the proportion of the cohort who own a Smartphone but also on the functionality of online questionnaires when completed on Smartphones. It is a challenge for methodological research to keep up with new and emerging data collection tools [30] .…”
Section: Discussionmentioning
confidence: 99%
“…Methods typically used for data collection in qualitative research include interviews and focus groups (either online, face‐to‐face, or by phone), participant diaries, or observations of interactions, including use of video to record day‐to‐day practice or events (Udtha, Nomie, Yu, & Sanner, ; Wilkerson, Iantaffi, Grey, Bockting, & Rosser, ). Advancements in digital and mobile technology are producing alternative methods for data collection with the benefits of smartphones, tablets, applications, and cloud‐based storage (Chan, Torous, Hinton, & Yellowlees, ; Dhiliwal & Salins, ; Faulds et al., ; Wilcox et al., ); however, they also bring design, implementation, and ethical challenges that need careful consideration.…”
Section: Traditional Qualitative Data Collection Strategiesmentioning
confidence: 99%